The Euler equations of an inviscid incompressible fluid driven by a Lévy noise. (December 2018) - Cyr, Justin; Tang, Sisi; Temam, Roger
Abstract: Our aim in this article is to show the local existence of pathwise solutions of the Euler equations driven by a general Lévy noise, in all space dimensions and for strictly positive time almost surely. The Euler equations are considered in a regular domain with slip boundary condition, or with periodic boundary conditions or in the whole space. In addition, we prove that when all data are C ∞ in space, so is the solution.